Design and analysis of a solar tower power plant integrated with thermal energy storage system for cogeneration - Sorgulu, Fatih; Dincer, Ibrahim (WILEY, 2019)
In the current study, a solar tower-based energy system integrated with a thermal energy storage option is offered to supply both the electricity and freshwater through distillation and reverse osmosis technologies. A high-temperature thermal energy storage subsystem using molten salt is considered for the effective and efficient operation of the integrated system. The molten salt is heated up to 565 degrees C through passing the solar tower. The thermal energy storage tanks are designed to store heat up to 12 hours. The temperature variations in the storage tanks are studied and compared accordingly for evaluation. The effect of operating temperatures on the freshwater production and overall system efficiency is determined. About 24.46 MW electricity is generated in the steam turbine under sunny conditions. Furthermore, the storage subsystem stores heat during sunny hours to utilize later in cloudy hours and night time. The produced power decreases to 20.17 MW in discharging hours due to temperature decrease in the tank. The electricity generated by the system is then used to produce freshwater through the reverse osmosis units and also to supply electricity for the residential use. A total flowrate of 240.02 kg/s freshwater is obtained by distillation and reverse osmosis subsystems.
Keywords: desalination; efficiency; energy; exergy; molten salt; solar energy; thermal energy storage; WATER DESALINATION; ELECTROLYZER; HYDROGEN; Energy & Fuels; Nuclear Science & Technology